2001
DOI: 10.1097/00005537-200108000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Tonsillectomy Bleeding: A Meta‐Analysis

Abstract: There is no difference in the rate of post-tonsillectomy bleeding in patients with abnormal coagulation studies as compared with patients with normal coagulation studies obtained preoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
162
2
17

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(190 citation statements)
references
References 15 publications
(11 reference statements)
8
162
2
17
Order By: Relevance
“…Regarding elective tonsillectomy for any condition, the data cover a wide range, but reasonable rates for readmissions seem to be between 0% and 7.8% and for reoperations between 0% and 3.8%. [6][7][8][9] In contrast to elective tonsillectomy, large series (reporting at least 100 patients) on PTH after quinsy tonsillectomy are rather rare (Table 3). High rates of PTH were reported by Dünne et al, 10 with an incidence of 25% for hospital readmission.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding elective tonsillectomy for any condition, the data cover a wide range, but reasonable rates for readmissions seem to be between 0% and 7.8% and for reoperations between 0% and 3.8%. [6][7][8][9] In contrast to elective tonsillectomy, large series (reporting at least 100 patients) on PTH after quinsy tonsillectomy are rather rare (Table 3). High rates of PTH were reported by Dünne et al, 10 with an incidence of 25% for hospital readmission.…”
Section: Discussionmentioning
confidence: 99%
“…5 The pooled rate of bleeding after tonsillectomy, a common pediatric procedure, has been reported as 3.3% in patients without bleeding disorders. 6 The identification of the child with pathologic bleeding may therefore prove difficult, given the relative frequency of nonpathologic bleeding and similarities between pathologic and nonpathologic bleeding. Common bleeding sites (eg, skin and mucous membranes) are similar, and whereas bleeding often occurs spontaneously in the setting of bleeding disorders, affected individuals may initially present with bleeding only after trauma or surgery or, in girls, at menarche.…”
mentioning
confidence: 99%
“…Moreover, they did not confirm any beneficial effect of antibiotic prophylaxis on the risk of secondary postoperative bleeding. On the basis of findings reported by Krishna and Lee [28], they suggested that secondary postoperative bleeding is mostly caused by fibrinolytic mechanisms associated with the degradation of fibrin, usually taking place on postoperative days 9-10. This was confirmed by Lowe and van der Meulen [18], who observed that the use of diathermy for tonsillectomy was associated with more severe tissue injury, a larger and thicker fibrin layer on the wound surface and a higher number of postoperative bleeding episodes.…”
Section: Discussionmentioning
confidence: 98%